The correlations of the equity markets in Asia and the impact of capital flow management measures - Pornpinun Chantapacdepong (Asian Development Bank Institute (ADBI), 2017)
This paper examines the international transmission of volatility in the stock markets of countries in emerging Asian economies (EAEs). The time period of the study is from before the Asian financial crisis until after the global financial crisis. Over two decades the degree of volatility interdependence of equity markets among Asian economies has been increasing. There has been stronger financial integration during calm periods, which could intensify the contagion effects across markets during turbulent times. The equity markets of the EAEs exhibit stronger correlations during the global financial crisis, confirming the existence of contagion and the intensification of systemic risk. The introduction of capital flow management (CFM) measures is associated with a reduction in the volatility dependence within the region.
Keywords: E42; E44; F32; G12; G15; 330; Economics